Ingestion of sodium plus water improves cardiovascular function and performance during dehydrating cycling in the heat. Issue 3 (17th December 2012) - Hamouti, N.; Fernández‐Elías, V. E.; Ortega, J. F.; Mora‐Rodriguez, R.
<x xml:space="preserve">Abstract</x> We studied if salt and water ingestion alleviates the physiological strain caused by dehydrating exercise in the heat. Ten trained male cyclists (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pghjspskbh" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />V˙O2m⁢ax</alternatives> : 60 ± 7 mL/kg/min) completed three randomized trials in a hot‐dry environment (33 °C, 30% rh, 2.5 m/s airflow). Ninety minutes before the exercise, participants ingested 10 mL of water/kg body mass either alone (CON trial) or with salt to result in concentrations of 82 or 164 mM Na+ (ModNa+ or HighNa+ trial, respectively). Then, participants cycled at 63% of <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pghjspskh3" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />V˙O2m⁢ax</alternatives> for 120 min immediately followed by a time‐trial. After 120 min of exercise, the reduction in plasma volume was lessened with ModNa+ and HighNa+ trials (−11.9 ± 2.1 and −9.8 ± 4.2%) in comparison with CON (−16.4 ± 3.2%; P < 0.05). However, heat accumulation or dissipation (forearm skin blood flow and sweat rate) were not improved by salt ingestion. In contrast, both salt trials maintained cardiac output (∼1.3 ± 1.4 L/min; P < 0.05) and stroke volume (∼10 ± 11 mL/beat; P < 0.05) above CON after 120 min of exercise. Furthermore, the salt trials equally improved time‐trial performance by 7.4% above CON (∼289 ± 42 vs 269 ± 50 W, respectively; P < 0.05). Our data suggest that pre‐exercise ingestion of salt plus water maintains higher plasma volume during dehydrating exercise in the heat without thermoregulatory effects. However, it maintains cardiovascular function and improves cycling performance.